PENGARUH MINAT BELAJAR FISIKA TERHADAP PRESTASI BELAJAR FISIKA SISWA - ANDRIONO MANALU; MARSINTA ROSALENA WATI SIALLAGAN; ROITA MELIANI NAIBAHO; RONAULI ENJELIA SILALAHI; ROSA VERAWATI MARBUN (JURNAL ILMIAH KOHESI, 2022)
The problem in this research is that the quality and quantity of education is still the most prominent problem, especially inphysics learning which is classified as a lesson that is difficult to understand and boring, resulting in low student physicslearning achievement. This research aims to find out the or absence of the influence of interest in studying physics on theachievement of learning physics students. This type of research is quantitative research. The study sample was 26 studentsof State High School 1 Aek Kuo. The instruments used in the study are questionnaires and tests about multiple options.The data analysis technique used is simple linear regression analysis. From the results of the calculation obtained t_hitung >t_tabel (2,657 > 2,056) with a significance level of 0.014. Thus it can be concluded that there is a significant positiveinfluence between the interests of studying physics to the achievement of learning physics students.